Utilization of PWM Signals in Automatic Parking Gate Speed Control Using PID System Modeling - Gustama, Ario; Hadikusuma, Ridwan Satrio; Hidayat, Rahmat (JTEV (Jurnal Teknik Elektro dan Vokasional), 2024)
Utilization of signals (Pulse Width Modulation) on the l298n motor driver and PID controller (Proportional Integral Derivative) is often used in industries, especially those that require robots as their automation medium, so that a process in robot automation does not only design system modeling, but is also required to implement a control system. angular position on a DC motor using the PID model. The PID control system in this study utilizes speed control with a PWM signal in the l298n motor driver and is applied as a DC motor angle position control module which is used for the parking doorstop system. The use of the trial error method is a suitable choice to be applied in finding values for the PID position control. This system keeps the speed and position in accordance with the set point when given a load as well as the ability of the system to catch up with the speed and position in order to reach the set point when the motor starts running are very important factors as a measure of speed and position control performance. because of its effectiveness, in the implementation of the parking gate latch produces a standard configuration of the PID controller with parameters Kp, Ki and Kd that can be determined so that the plant characteristics match the expected design criteria. In the trial error method, the most effective value was obtained with Kp = 10, Ki, 1.9 and Kd = 0.8 which resulted in steady state and no overshoot.